2014
DOI: 10.4028/www.scientific.net/msf.778-780.742
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Trenched and High Temperature Annealed 4H-SiC

Abstract: This study focuses on the effects of a high temperature anneal after dry etching of trenches (post-trench anneal, PTA) on 4Hsilicon carbide (4H-SiC). We aim at the optimum 4H-SiC post-trench treatment with respect to the fabrication and the operation of a trenched gate metal oxide semiconductor field effect transistor (Trench-MOSFET). PTA significantly reduces micro-trenches, also called sub-trenches [, in the corners of the bottom of the trench. This is highly beneficial in case the etched trench sidewall is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 5 publications
(5 reference statements)
0
2
0
Order By: Relevance
“…It is assumed that etching defects are not sufficiently annealed using the 'low anneal temperature' during the PTP, which goes along with minor smoothed etch profiles. By contrast, edges at the upper and at the lower part of the trenched sidewalls are rounded distinctly if a 'high anneal temperature' is used [3], see Fig. 2.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…It is assumed that etching defects are not sufficiently annealed using the 'low anneal temperature' during the PTP, which goes along with minor smoothed etch profiles. By contrast, edges at the upper and at the lower part of the trenched sidewalls are rounded distinctly if a 'high anneal temperature' is used [3], see Fig. 2.…”
mentioning
confidence: 98%
“…Furthermore, it is shown that an inert gas anneal, either performed at low temperature or at high temperature, accounts for a low quality MOS interface as the transition region between accumulation and depletion is stretched out. It is assumed that these depletion phenomena originate from a near-surface excess of carbon due to the sublimation of Si atoms during the high temperature anneal process [3,5]. Fig.…”
mentioning
confidence: 99%